Enhanced disclosure environment and stock dividend/split in China. Issue 4 (23rd February 2021) - Wang, Guojun; Wang, Yuetang; Yang, Dan; Zhang, Lu; Zhu, Qingjing
ABSTRACT: This paper examines changes in firm behaviour around a regulatory change regarding stock dividend/split in China which mandates enhanced disclosure of such activities. Firms announce significantly fewer stock dividends/splits in the enhanced disclosure environment. The enhanced disclosure also improves the link of stock dividend/split activities with firm growth. Investors react less positively to stock dividend/split announcements in the enhanced disclosure environment. The findings suggest that more cautious announcement strategies and more rational investor reactions are consistent with a decline in false signalling.